THE CONSTRUCTION OF THE MUSEOLOGICAL OBJECT (Cadernos de Sociomuseologia, 2009)
"Exhibiting is or should be to work against ignorance, especially against the most refractory of all ignorance: the pre-conceived idea of stereo typed culture. To exhibit is to take a calculated risk of disorientation - in the etymological sense : ( to lose your bearings), disturbs the harmony, the evident , and the consensus, that constitutes the common place ( the banal). Needless to say however it is obvious that an exhibition that deliberately tries to scandalise will create an inverted perversion which results in an obscurantist pseudo-luxury - culture ... between demagogy and provocation, one has to find visual communication's subtle itinerary. Even though an intermediary route is not so stimulating : as Gaston Bachelard said "All the roads lead to Rome, except the roads of compromise." (1)